2014
DOI: 10.1007/s00429-014-0920-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term proper name anomia after removal of the uncinate fasciculus

Abstract: The functional organization of left and right hemispheres is different, and hemispheric asymmetries are thought to underlie variations in brain function across individuals. In this study, we assess how differences between hemispheres are reflected in Asymmetric Functional Connectivity (AFC), which provides a full description of how the brain's connectivity structure during resting state differs from that of the same brain mirrored over the longitudinal fissure. In addition, we assess how AFC varies across subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 62 publications
2
39
3
Order By: Relevance
“…Yet, such a distribution can be attributed to the role of the UF in the semantic processing (Dick and Tremblay, 2012; Chang et al, 2015) and in the proper name retrieval process (Papagno, 2011). Therefore, if semantic connections reflect its role in the ventral stream, hesitation and no response errors could be interpreted as an expression of anomia, that has been reported as a consequence of UF resection or damage (Papagno et al, 2011, 2016). These data further increased our confidence in the nTMS-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, such a distribution can be attributed to the role of the UF in the semantic processing (Dick and Tremblay, 2012; Chang et al, 2015) and in the proper name retrieval process (Papagno, 2011). Therefore, if semantic connections reflect its role in the ventral stream, hesitation and no response errors could be interpreted as an expression of anomia, that has been reported as a consequence of UF resection or damage (Papagno et al, 2011, 2016). These data further increased our confidence in the nTMS-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on patients during awake neurosurgery for left lateralized gliomas have demonstrated that removal of the UF leads to severe impairment in the ability to retrieve the names of famous faces, both post-surgery and at a 3 month follow-up (Papagno et al, 2011). In a recent extension by the same research group, proper naming deficits remained 12 months post-surgery (Papagno et al, 2014). Similar findings have been reported in other laboratories and replicated across different techniques (Damasio, Grabowski, Tranel, Hichwa, & Damasio, 1996; Drane et al, 2008; Grabowski et al, 2001; Nomura et al, 2013; Tranel, Damasio, & Damasio, 1997), suggesting a robust link between proper name retrieval and the UF.…”
Section: Introductionmentioning
confidence: 97%
“…It has been hypothesized that the UF is part of the ventral language pathway, supporting object naming by relaying sensory information about objects, processed in the ventral temporal cortex, to language regions in the inferior-lateral frontal lobes (Papagno et al, 2014a). Evidence for this view is mixed.…”
Section: Introductionmentioning
confidence: 99%